Development of New Contrast Agents for Imaging Function and Metabolism by Magnetic Resonance Imaging. (24th July 2017) - Carvalho, Alexandra; Gonçalves, M Clara; Corvo, M Luísa; Martins, M Bárbara F
Liposomes are interesting nanosystems with a wide range of medical application. One particular application is their ability to enhance contrast in magnetic resonance images; when properly loaded with magnetic/superparamagnetic nanoparticles, this means to act as contrast agents. The design of liposomes loaded with magnetic particles, magnetoliposomes, presents a large number of possibilities depending on the application from image function to metabolism. More interesting is its double function application as theranostics (diagnostics and therapy). The synthesis, characterization, and possible medical applications of two types of magnetoliposomes are reviewed. Their performance will be compared, in particular, their efficiency as contrast agents for magnetic resonance imaging, measured by their relaxivities r 1 and r 2 relating to their particular composition. One of the magnetoliposomes had 1, 2-diacyl-sn-glycero-3-phosphocholine (soy) as the main phospholipid component, with and without cholesterol, varying its phospholipid to cholesterol molar ratios. The other formulation is a long-circulating liposome composed of 1, 2-diacyl-sn-glycero-3-phosphocholine (egg), cholesterol, and 1, 2-distearoyl-sn-glycerol-3-phosphoethanolamine- N -[methoxy(polyethylene glycol)-2000]. Both nanosystems were loaded with superparamagnetic iron oxide nanoparticles with different sizes and coatings.